Activating Transcription Factor 5 Promotes Tumorigenic Capability in Cervical Cancer Through the Wnt/β-Catenin Signaling Pathway - Shi F; Wei Y; Huang Y; Yao D (Cancer Management and Research)
Fengjuan Shi,1,2 Yumei Wei,2 Yingmei Huang,2 Desheng Yao1 1Department of Gynecologic Oncology, Guangxi Medical University Cancer Hospital, Nanning, Guangxi, People’s Republic of China; 2Department of Gynecology, the Fifth Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of ChinaCorrespondence: Desheng Yao, Email yaodesheng@gxmu.edu.cnPurpose: Cervical cancer is the fourth leading cause of cancer-related death in women. Furthermore, owing to its significant risk of recurrence or metastasis, the overall prognosis of patients with cervical cancer remains poor. Activating transcription factor 5 (ATF5) plays a crucial role in cell proliferation, survival, and apoptosis, and has been implicated in the progression of various types of cancer. However, the biological function and precise mechanism of ATF5 in cervical cancer remain unclear. This study, aimed to explore the function of ATF5 and its potential mechanisms in cervical cancer.Patients and Methods: Quantitative real-time PCR, Western blot and immunohistochemistry were used to detect the expression of ATF5 in cervical cancer tissues and cell lines. Knockdown ATF5 expression in cervical cancer cell lines was constructed using lentivirus-mediated shRNA to explore the role of ATF5 in cervical cancer through cell viability, transwell, and wound healing experiments. The expression of Wnt3a and β-catenin were investigated using quantitative real-time PCR and Western blot.Results: ATF5 was overexpressed in cervical cancer, and upregulation of ATF5 expression was associated with a poor prognosis. ATF5 knockdown inhibited the proliferation, migration and invasion abilities of cervical cancer cells. Furthermore, the downregulation of ATF5 led to the suppression of Wnt3a and β-catenin expression, which are key molecules in the Wnt/β-catenin signaling pathway.Conclusion: ATF5 promotes tumorigenic capability in cervical cancer through the Wnt/β-catenin signaling pathway. ATF5 may be a potential prognostic biomarker and therapeutic target in the management of cervical cancer.Keywords: activating transcription factor 5, cervical cancer, Wnt/β-catenin signaling pathway, tumorigenicity, prognosis